Causalidade entre microcrédito e mercado informal: uma análise do Programa Crediamigo - Silva, Roberto Pereira da (2018)
The study in question is intended to know the direction of causality between informality and microcredit in the Northeast region. The creation in the 1990s of CrediAmigo, a solidarity credit program analyzed in the research and the evidence of a growth in the process of informalization, in the same period, justify a study that relates these two aspects. The analysis is based on a data panel, containing information on the volume borrowed by CrediAmigo, in millions of Reais, and the degree of informality, for the nine states of the investigated region. The model is estimated according to the methodology proposed by Arellano and Bond (1991). As a result it is found that informality causes the volume borrowed by CrediAmigo, but credit does not cause informality. Considering that there are not so many papers in the line of informalitymicrocredit research, the study in question could serve as a theoretical reference for future analyzes.